Telomere Attrition in Neurodegenerative Disorders - Levstek, Tina; Kozjek, Eva; Dolžan, Vita; Trebušak Podkrajšek, Katarina (Frontiers in Cellular Neuroscience, 2020)
Telomere attrition is increased in various disorders and is therefore a potential biomarker for diagnosis and/or prognosis of these disorders. The contribution of telomere attrition in the pathogenesis of neurodegenerative disorders is yet to be fully elucidated. We are reviewing the current knowledge regarding the telomere biology in two common neurodegenerative disorders, Alzheimer’s disease and Parkinson’s disease. Furthermore, we are discussing future prospective of telomere research in these disorders. The majority of studies reported consistent evidence of the accelerated telomere attrition in Alzheimer’s disease patients, possibly in association with elevated oxidative stress levels. On the other hand in Parkinson’s disease, various studies reported contradictory evidence regarding the telomere attrition. Consequently, due to the low specificity and sensitivity, the clinical benefit of telomere length as a biomarker of neurodegenerative disease development and progression is not yet recognized. Nevertheless, longitudinal studies in large carefully selected cohorts might provide further elucidation of the complex involvement of the telomeres in the pathogenesis of neurodegenerative diseases. Telomere length maintenance is a complex process characterized by environmental, genetic and epigenetic determinants. Thus, in addition to the selection of the study cohort, also the selection of analytical methods and types of biological samples for evaluation of the telomere attrition is of outmost importance.